Algorithm S Setting the target standard deviation for proficiency testing assessment by Algorithms - Aupaiboon, Wannee; Hemapattawee, Rachada; Tagheen, Pochaman (Bulletin of Applied Sciences, 2015)
This study aims to determine the target standard deviation for proficiency assessment of total dissolved solids in water scheme. Standard deviations from previous proficiency schemes which conducted during 2008 to 2014 at the concentration range of 300 - 400 mg/L were collected. The target standard deviations for proficiency assessment were calculated using Algorithm S (ISO 13528:2005) approach. It is found that the target standard deviation is 5.0 %RSD. This is corresponding with the technical criteria for evaluate laboratories' performance. Acceptable target standard deviation in the same range of the sample concentration was achieved. This approach can be applied to the other concentration range and other sample matrix for proficiency testing scheme.